Intralesional radiofrequency treatment for venous lake. (16th April 2019) - Poonia, Kavita; Kumar, Anand; Thami, Gurvinder P.
Abstract: Background: Venous lakes are asymptomatic, cosmetically unacceptable vascular malformations commonly present over the lips. Most of the lesions do not warrant any therapeutic intervention. Objective: We herein report a 20‐year‐old male patient with venous lake who was treated using intralesional radiofrequency (RF) by modified insulated intravenous cannula as an extended probe. Methods: An RF ablation was performed under local infiltration anesthesia using intravenous infusion cannula as an extended insulated probe to deliver current. Results: The venous lake was obliterated immediately post‐procedure with minimal inflammatory change. It showed good cosmetic results with minimal scarring and no recurrence at 18 months of follow‐up. Conclusions: Intralesional RF using modified insulated probe is a useful alternative treatment and may be considered to treat small venous lakes.